2017
DOI: 10.1002/lio2.91
|View full text |Cite
|
Sign up to set email alerts
|

Third‐generation bisphosphonates for cochlear otosclerosis stabilizes sensorineural hearing loss in long‐term follow‐up

Abstract: ObjectiveTo assess long‐term hearing outcomes in patients treated with third‐generation bisphosphonates for otosclerosis‐related progressive sensorineural hearing loss (SNHL).Study DesignRetrospective case series reviewMethodsWe performed a retrospective case series review of patients with otosclerosis and progressive SNHL. Patients were treated with either risedronate or zoledronate after a diagnosis of otosclerosis with a significant SNHL component. Bone conduction pure tone threshold averages (BC‐PTAs) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 28 publications
0
25
0
Order By: Relevance
“…Moreover, these findings in mice supported the effect of zoledronate, which is approved for the treatment of osteoporosis and related bone diseases (Pazianas and Abrahamsen, 2011), as an off-label treatment in otosclerosis, a disease characterized by pathologic remodeling of the cochlear bone (Quesnel et al, 2012). Because word recognition is a sensitive metric of cochlear neural function, a surprising clinical observation (Quesnel et al, 2012;Jan et al, 2017) that bisphosphonates could stabilize SNHL and improve word recognition scores in patients with otosclerosis, together with our previous results on the influence of the drug on cochlear sensory cells (Kao et al, 2013), prompted us to assess the effects of bisphosphonates on cochlear synaptopathy.…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…Moreover, these findings in mice supported the effect of zoledronate, which is approved for the treatment of osteoporosis and related bone diseases (Pazianas and Abrahamsen, 2011), as an off-label treatment in otosclerosis, a disease characterized by pathologic remodeling of the cochlear bone (Quesnel et al, 2012). Because word recognition is a sensitive metric of cochlear neural function, a surprising clinical observation (Quesnel et al, 2012;Jan et al, 2017) that bisphosphonates could stabilize SNHL and improve word recognition scores in patients with otosclerosis, together with our previous results on the influence of the drug on cochlear sensory cells (Kao et al, 2013), prompted us to assess the effects of bisphosphonates on cochlear synaptopathy.…”
Section: Introductionmentioning
confidence: 68%
“…This double-blind prospective study showed a non-significant trend toward hearing stabilization and improvement in the etidronate group compared to the placebo group ( Kennedy et al, 1993 ). In a 9-year follow-up study at our institution, patients with cochlear otosclerosis treated with the third-generation bisphosphonate zoledronate showed stabilization or improvement of SNHL and did not exhibit any side effects ( Jan et al, 2017 ). Despite the broad use of bisphosphonates, there are only three reported cases of ototoxicity after etidronate or pamidronate therapy ( Reid et al, 1995 ; Yasil et al, 1998 ).…”
Section: Discussionmentioning
confidence: 99%
“…The other studies utilizing the same subject population were two double-blind RCTs by de Oliveira Vicente et al in 2012 12 and 2015. 13 Unlike the Jan et al 14 The treatment period was 6 months. The 2012 report compared air and bone conduction thresholds, air bone gap, speech recognition threshold, and speech discrimination between groups and within each group pre-and post-treatment.…”
Section: Resultsmentioning
confidence: 96%
“…One pair of linked studies includes the study from Jan et al, 14 which is a long-term follow-up of Quesnel et al rate of change in disease progression in the year just prior to the experiment (1-year pretreatment data) as well as the overall progression (first available data). Both the 2012 and 2017 studies used a ±10 dB as a significant change in bone conduction thresholds.…”
Section: Resultsmentioning
confidence: 99%
“…A double‐blind clinical trial found a nonsignificant trend toward stabilization or improvement in air conduction thresholds at 1 and 4 kHz after treatment with etidronate 14 . A small study of patients with otosclerosis and progressive hearing loss before treatment was suggestive of stabilization of hearing thresholds and word recognition scores after zoledronate treatment, but there was no control group for comparison 44 . A promising study in noise‐exposed mice found zoledronate reversed noise‐induced damage to primary afferent auditory synapses and subsequent recovery of peripheral auditory function.…”
Section: Discussionmentioning
confidence: 99%